Family Involvement in Strengthening Character Education: Integrating Sundanese Values and the Merdeka Curriculum - Jamaluddin Jamaluddin; Ahmad Sukandar (Urwatul Wutsqo: Jurnal Studi Kependidikan dan Keislaman, 2025)
This study aims to analyze family involvement in strengthening character education through the integration of Sundanese cultural values within the implementation of the Merdeka Curriculum at SDN 2 Cibodas, Cimahi City. Using a descriptive qualitative approach and an intrinsic case study design, the research involved four months of participant observation, in-depth interviews with 15 parents, 6 teachers, and 10 students, as well as document analysis from school and community sources. The findings reveal that family involvement in character education remains limited due to economic constraints—41.2% of parents earn IDR 1–2 million per month—and long working hours, resulting in a 34% rate of student indiscipline. Sundanese values such as silih asih, silih asah, and silih asuh serve as moral anchors but have declined by 40% due to digital media exposure. The integration of the Merdeka Curriculum through the Pancasila Student Profile Strengthening Project offers an opportunity to revitalize local wisdom via a hybrid collaboration model between families and schools. Theoretically, this study extends Bronfenbrenner’s Ecological Theory by incorporating digital literacy and school infrastructure as mediating variables, while practically proposing a local-culture-based family–school synergy model to reinforce students’ character development in urban settings